Mining of disease-resistance genes in Crocus sativus based on transcriptome sequencing - Ye, Dongdong; Zhang, Siwei; Gao, Xiankui; Li, Xiujuan; Jin, Xin; Shi, Min; Kai, Guoyin; Zhou, Wei (Frontiers in Genetics, 2024)
Crocus sativus L. has an important medicinal and economic value in traditional perennial Chinese medicine. However, due to its unique growth characteristics, during cultivation it is highly susceptible to disease. The absence of effective resistance genes restricts us to breed new resistant varieties of C. sativus. In present study, comprehensive transcriptome sequencing was introduced to explore the disease resistance of the candidate gene in healthy and corm rot-infected C. sativus. Totally, 43.72 Gb of clean data was obtained from the assembly to generate 65,337 unigenes. By comparing the gene expression levels, 7,575 differentially expressed genes (DEGs) were primarily screened. A majority of the DEGs were completely in charge of defense and metabolism, and 152 of them were annotated as pathogen recognition genes (PRGs) based on the PGRdb dataset. The expression of some transcription factors including NAC, MYB, and WRKY members, changed significantly based on the dataset of transcriptome sequencing. Therefore, this study provides us some valuable information for exploring candidate genes involved in the disease resistance in C. sativus.